The Effectiveness of Banking Countercyclical Policies in the Development of Priority Economic Sectors in Indonesia - Muh Rudi Nugroho; Akhmad Syakir Kurnia (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2021)
Economic development leads to the evolution and improvement of the financial system. In particular, banks grew relatively larger than national output in line with economic developments. This study aims to analyze how banking policy can cause multiplier effects for the macroeconomic sector and be able to reduce the procyclicality of the banking sector with economic growth that touches the aspect of reverse causality. To answer this concern, many international forums approved the formation of documents one of which includes macroprudential aspects by developing countercyclical capital buffer (CCB) indicators that function to monitor the level of procyclicality of the financial system. The research period used is quarterly data from 2010Q1 to 2019Q4. The analytical tool used is structural vector autoregression (SVAR). Based on the results of the impulse response function, all macroeconomic variables used in this study, namely real GDP, inflation, investment, and the exchange rate respond negatively to CCB policies in conventional banks, Islamic banks, and both. The biggest contribution of the three bank models is to the investment variable. Based on the results of sector mapping, it was found that the direction of the development of Indonesia's priority sectors was in the secondary sector or business fields related to the processing industry, such as both food and beverage, clothing and textiles, and chemicals. Public and foreign public confidence in the products of the processing industry in Indonesia is certainly inseparable from the guarantee of certainty in doing business and investment security that will increase the flow of private capital, especially foreign direct investment. This investment security guarantee is an effect of good financial capital liquidity.